Вычислите значение выражения [latex]( \frac{4}{7} )^{2} * 1 \frac{3}{4} - (-3) ^{3} = 2^{3} *0,5 ^{3}+ (-2,47) ^{0}= 19 ^{7} * (19 ^{2} ) ^{3} : 19^{11} = \frac{4 ^{6} }{8 ^{3} } =[/latex]
Вычислите значение выражения
[latex]( \frac{4}{7} )^{2} * 1 \frac{3}{4} - (-3) ^{3} =
2^{3} *0,5 ^{3}+ (-2,47) ^{0}=
19 ^{7} * (19 ^{2} ) ^{3} : 19^{11} =
\frac{4 ^{6} }{8 ^{3} } =[/latex]
Ответ(ы) на вопрос:
16/49*7/4 + 27 = 64/196 + 27 = 16/49 + 27 = 27 16/49 = 1339/49
8*1/8-1=1-1=0
19⁷*19⁶/19¹¹=19¹³/19¹¹=19²=381
4⁶/8³=2¹²/2⁹=2³=8
(4/7)² * 1 3/4 - (-3)³ = 16/49 * 7/4 - (-27) = 4/7 + 189/7 = 193/7 = 27 4/7
2³ * 0,5³ + (-2,47)⁰ = 8 * 0,125 + 1 = 1+1= 2
19⁷ * (19²)³ : 19¹¹ = 19⁷ * 19⁶ : 19¹¹ = 19¹³ : 19¹¹ = 19² = 361
4⁶ / 8³ = 2¹² / 2⁹ = 2³ = 8
Не нашли ответ?
Похожие вопросы